Detection of the dietary xenoglycan N-glycolylneuraminic acid (Neu5Gc) and anti-Neu5Gc antibodies within reproductive tracts of male and female infertility subjects. Issue 3 (2015) - Sroga, Julie M; Wu, Diana H; Ma, Fang; Tecle, Eillen; Ressler, Ilana B.; Maxwell, Rose; Ferrari, Rachael; Whigham, Leah; Gagneux, Pascal; Lindheim, Steven R.
No abstract available